Analysis of Flow Through Extra-Anatomic Bypasses Between Supra-Aortic Branches Using Particle Image Velocimetry (PIV). - Williamson, Petra N.; Docherty, Paul D.; Khanafer, Adib; Steven, Briana M. (Clinical Medicine Insights: Cardiology, 2024)
Supra-aortic extra-anatomic debranch (SAD) are prosthetic surgical grafts used to revascularize head and neck arteries that would be blocked during a surgical or hybrid procedure used in treating ascending and arch of the aorta pathologies. However, bypassing the supra-aortic arteries but not occluding their orifice might introduce potential for competitive flow that reduces bypass patency. Competitive flow within the bypasses across the supra-aortic arteries has not previously been identified. This research identified haemodynamics due to prophylactic inclusion of bypasses from the brachiocephalic artery (BCA) to the left common carotid artery (LCCA), and from the LCCA to left subclavian artery (LSA). Four model configurations investigated the risk of competitive flow and the necessity of intentionally blocking the proximal LSA and/or LCCA. Particle image velocimetry (PIV) was used to assess haemodynamics in each model configuration. We found potential for competitive flow in the BCA-LCCA bypass when the LSA was blocked, in the LSA-LCCA bypass, when the LCCA alone or LCCA and LSA were blocked. Flow stagnated at the start of systole within the RCCA-LCCA bypass, along with notable recirculation zones and reciprocating flow occurring throughout systolic flow. Flow also stagnated in the LCCA-LSA bypass when the LCCA was blocked. There was a large recirculation in the LCCA-LSA bypass when both the LCCA and LSA were blocked. The presence of competitive flow in all other configurations indicated that it is necessary to block or ligate the native LCCA and LSA once the debranch is made and the thoracic endovascular aortic repair (TEVAR) completed.